Coming of Age in Contemporary Pakistan: Influences of Gender and Poverty (The Pakistan Development Review, 2003)
Economic development is strongly connected to the longevity, growth and structure of country’s population [Bloom and Canning (2003)]. Pakistan currently has the largest cohort of young people in its history (25 million aged 15-24, Census 1998) that has serious implications for the provision of schooling, health services and adequate jobs. Therefore the well being of these valuable young cohorts is profoundly important for the social and economic development and prosperity of Pakistan [Population Council (2003)]. This demographic lift can promote economic lift-off [Bloom and Canning (2003)]. In fact, Pakistan will face dire consequences if this resource is not capitalised and young people remain uneducated and unskilled [Faizunnisa and Ikram (2003)]. Work is one of the key transitions in the lives of young people. It is an important marker of adulthood, with strong implications for a country’s social and economic development. Work depending on its nature and remuneration can be the most important factor shaping adult lives. Youth employment has many implications for the labour market, poorer households and for the youth themselves.